The effects of fermentation process on the chemical composition and biological activity of spider flower (Gynandropsis gynandra) - Muhialdin, Belal J.; Sukor, Rashidah; Ismail, N.; Ahmad, S. W.; Che Me, N.; Meor Hussin, Anis Shobirin (Bhopal Journal of pure and applied microbiology, 2018)
Spider flower (Gynandropsis gynandra), also known as “Maman” that is traditionally fermented and consumed as pickles in Malaysia. In this study, the chemical composition, microbiological content and biological activities of the fresh and fermented Maman leaves and stem were evaluated. Approximate analysis was carried out by using AOAC standard methods, microbial content was determined by using total plate count, antioxidant activity was evaluated DPPH (%) and ferric reducing power. The antimicrobial activity evaluated by 96 well micro-titer plates against Salmonella Typhimurium ATCC14028, Escherichia coli ATCC12229 and Staphylococcus aureus ATCC6538. The results demonstrated reduction in the protein, fiber, and carbohydrate contents of Maman sample after fermentation in both leaves and stem, while the content of ash was increased. Fermented Maman contained significantly high(p<0.05) number of anaerobic bacterial count which is 5.5600 log CFU/mL for the stem and 5.4633 log CFU/mL for the leaves. The aerobic bacterial count was reduced significantly after the fermentation by approximately two logs. The antioxidant activity, phenolic compounds, and flavonoids content of fresh Maman was slightly higher than the fermented samples. The fermented Maman samples demonstrated 90% growth inhibition towards selected pathogens, while fresh samples showed less than 50% bacterial growth inhibition. This indicates that natural fermentation process improved the nutrient content and the biological activity of Maman.